O significado e o sentido de sucesso e/ou fracasso em relação à dinâmica da inclusão/exclusão escolar: um estudo sobre o desempenho escolar com professores e alunos - Cassoli, Raquel Alves (2017)
This thesis stems from the concerns of the researcher about the meanings of success and/or failure in school inclusion/exclusion situations reported both by teachers and by pupils in the school space. This is because it is known that, socially, success and failure are meanings of ideological form, constituting meanings by pupils, and teachers not articulated the fame, money and merit or rejection, denial and failure, for example. Considering the school, as described by Charlot (2013), a place that plays the ideology, this research aims to, in general, to capture and analyze the production process of the meanings, i.e. the senses and meanings of teachers and students about failure and/or school success in situations of inclusion/exclusion in different realities, as well as the relations established between them. For both used focus groups held with teachers and students, at different times, a public school in the city of São Paulo and a private school in the State of São Paulo in Brazil. The theoretical framework that guides and methodologically this is the study of Psychology Historical Partner, which is based on dialectical and historical materialism, especially through its precursors Russians: Vygotsky, Luria and Leontiev. The reference for the analysis of the study opted for the test procedure and interpretation called nuclei of meaning (AGUIAR; OZELLA 2013; AGUIAR; SOARES; MACHADO, 2015). In the analysis of data built success push your notion personal fulfilment and the feeling of happiness that acts as a currency that assigns the value of success. These mark the notions and experiences qualify the capitalist society. In case of inclusion of disabled children in regular education, the effort needs to be increased and the process loads the suffering political exclusion itself unethical. The study subjects attach a success the disabled that is revealed as part of a process, which is not reached in your completeness and is not regarded as well-deserved achieve happiness. The school performance as a learning and development process is little considered, once the mark of success is given by the result reached as good grades and exams